Nucleotide diversity of genes related to chlorogenic acid biosynthesis of coffea - Ivamoto, Suzana Tiemi; Pot, David; Lannes, Sergio Dias; Domingues, Douglas Silva; Vieira, Luiz Gonzaga Esteves; Pereira, Luiz Filipe Protasio (Coffee Science - ISSN 1984-3909, 2013)
Chlorogenic acids (CGAs) are important chemical compounds of Coffea spp. related to beverage quality as they affect its astringency and can change its aroma and flavor. About 310,000 Coffea Expressed Sequence Tags (ESTs) are available and provide access to the nucleotide variability of the plant and to the development of molecular markers linked to beverage quality for the main enzymes involved in biosynthesis of the CGAs: PAL, C4H, 4CL, CQT and C3’H. In this study we identified SNP, INDELS and SSR polymorphisms within the nucleotide sequences available from the Brazilian Coffee Genome database and from the NCBI. The EST sequences for CGAs were trimmed and clustered by the program Codon Code Aligner, and polymorphisms and their validation detected (chromatogram quality). We identified six isoforms for PAL, one for C4H, six for 4CL, two for CQT and two for C3’H. The contigs formed exhibited a total of 248 polymorphisms (236 SNPs and 12 INDELs), with 201 in the coding region (127 non-synonymous and 74 synonymous). The frequency of polymorphisms was greater in the UTR regions (1pol/54pb) in relation to the coding region (1pol/81pb). The analysis of C. arabica sequences allowed identification of two different subgroups of sequences, related to their ancestral genomes (C. canephora and C. eugenioides). The presence of 67,4% of the polymorphisms between the ancestral groups and 32,6% within the groups were observed em C. arabica . The characterization of nucleotide diversity on those genes is essential for further studies on differential expression of their homeologs, as well as the use of CGAs as molecular markers related to genetic mapping.